Cryobanking of Fish and Shellfish Egg, Embryos and Larvae: An Overview - Diwan, Arvind D.; Harke, Sanjay N.; Gopalkrishna,; Panche, Archana N. (Frontiers in Marine Science, 2020)
Number of attempts has been made to cryopreserve fish and shellfish gametes and success has been achieved to establish only sperm banks in case of some commercially important fish. In shellfish also particularly in shrimps though the sperm cryopreservation was successful, no attempts were made to develop sperm banks. As far as cryobanking of egg and embryos of fish and shellfish is concerned, less research efforts were made that too with limited success. Number of reasons has been given for the failure of egg /embryo cryopreservation and the main barriers speculated are low membrane permeability in the eggs, and the large yolk mass of the oocyte and the presence of compartments in early developing embryos. Both these factors result in ice crystal formation during the freezing process. In addition, the oocytes and embryos are prone to chilling injuries unrelated to ice crystal damage. There are number of other problems reported by several workers in the egg/embryo cryobanking protocols which are elaborately discussed in the present paper. There is an urgent need to develop a viable cryobanking technology for fish egg/embryos to enhance fish production in captive condition. Attempt to cryopreserve larvae of aquatic animals is another challenge coming up in recent past. The purpose of the present review is to collect comprehensive information on the efforts so far made on fish and shellfish egg and embryo cryobanking, assess the challenges in the development of viable technology and plan for future research for making this technology viable and cost effective.